Partnering portfolios, value-creation logics, and growth trajectories : a comparison of Yahoo and Google (1995 to 2007) - Rindova, Violina P. (2013)
We add to the theory of entrepreneurial firm growth by inductively theorizing the processes through which new high-growth firms utilize their partnering portfolios to pursue distinctive approaches to growth. We extend the strategic perspective on entrepreneurial networks by identifying three mechanisms linking partnering portfolios to differences in firm growth: configuring partnering portfolios to pursue distinctive logics for sourcing external resources, aligning resource-sourcing and resource-linking logics in new product development, and embarking on different growth trajectories, which contribute to different performance patterns. These theoretical insights contribute to current understanding of the external and internal sources of heterogeneity in the performance of entrepreneurial firms.